Hubungan motivasi belanja online fashion dengan akses informasi instagram - Rahmadin Rahmadin; Prijana Prijana; Andri Yanto (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
[Correlation between Online Shopping Motivation and Information Access in Instagram]. This study aims to find the correlation between shopping online fashion motivation using two variables (1) hedonic shopping motivation and (2) utilitarian shopping motivation with information access in instagram of the students of Faculty of Communication Sciences Padjadjaran University. The method used in this research is correlational with quantitative approach. The population in this study are students of faculty of communication in 2014 and 2015 who has access to online shop fashion in instagram. The sampling technique used in this study is an accidental sampling that produced sample of 92 respondents. Data analyze using Pearson correlation. Results show that correlation between shopping online fashion motivation with information access in instagram is high, with correlation coefficient 9,80 while ttable 1,291 , the tcount greater than ttable (9,80) > (1,291), then H0 is rejected and H1 is accepted. The conclusions of this study is online shopping fashion motivation has a significant correlation with information access in instagram.